Assessing advantages of sequential boron neutron capture therapy (BNCT) in an oral cancer model with normalized blood vessels - Molinari, Ana Julia (2014)
BACKGROUND: We previously demonstrated the therapeutic success of sequential boron neutron capture therapy (Seq-BNCT) in the hamster cheek pouch oral cancer model. It consists of BPA-BNCT followed by GB-10-BNCT 24 or 48 hours later. Additionally, we proved that tumor blood vessel normalization with thalidomide prior to BPA-BNCT improves tumor control. The aim of the present study was to evaluate the therapeutic efficacy and explore potential boron microdistribution changes in Seq-BNCT preceded by tumor blood vessel normalization. MATERIAL AND METHODS: Tumor bearing animals were treated with thalidomide for tumor blood vessel normalization, followed by Seq-BNCT (Th+ Seq-BNCT) or Seq-Beam Only (Th+ Seq-BO) in the window of normalization. Boron microdistribution was assessed by neutron autoradiography. RESULTS: Th+ Seq-BNCT induced overall tumor response of 100%, with 87 (4)% complete tumor response. No cases of severe mucositis in dose-limiting precancerous tissue were observed. Differences in boron homogeneity between tumors pre-treated and not pre-treated with thalidomide were observed. CONCLUSION: Th+ Seq-BNCT achieved, for the first time, response in all treated tumors. Increased homogeneity in tumor boron microdistribution is associated to an improvement in tumor control.